53.9k views
2 votes
(6,3*10^-2)÷(2,1*10^4​

User Piacenti
by
5.1k points

2 Answers

3 votes

Answer:


3* {10^(-6)}

Explanation:


(6.3 * 10^(-2))/(2.1 * 10^4)


=(6.3 )/(2.1)* (10^(-2))/(10^4)


=3* (10^(-2))/(10^4)


\textsf{Apply exponent rule} \quad (a^b)/(a^c)=a^(b-c):


=3* {10^((-2-4))}


=3* {10^(-6)}

User Nicolas Reynis
by
4.8k points
6 votes

Answer:


  • 3*10^(-6) or
    0.000003

Given expression:


  • (6.3*10^(-2)) : (2.1*10^4)

Simplify it in steps below:


  • (6.3*10^(-2)) : (2.1*10^4) =

  • (6.3 :2.1)*(10^(-2):10^4)=

  • 3*(10^(-2-4))=

  • 3*10^(-6) or
    0.000003

Used properties:


\cfrac{ab}{cd}=\cfrac{a}{c}*\cfrac{b}{d}


a^b:a^c=a^(b-c)


a^(-b)=1/a^b

User Knalli
by
5.4k points